Penerapan IoT Dalam Mendukung Konsep Smart School Melalui Sistem Bel Sekolah Otomatis - dakota fathir; fatoni (PPPM Institut Teknologi Pagar Alam, 2026)
Academic time management is a crucial aspect in maintaining discipline and order in school learning activities. However, school bell systems that are still operated manually are prone to delays and operational errors due to human factors. This study aims to implement Internet of Things (IoT) technology to support the Smart School concept through the development of an automatic school bell system. The research employed a system engineering approach using a case study method with the Waterfall development model, which consists of the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using an ESP32 microcontroller as the main controller, time synchronization based on the Network Time Protocol (NTP), and a DFPlayer Mini module with speakers as audio output devices. System testing was conducted using the black box testing method to evaluate the main system functionalities, as well as user acceptance testing (UAT) involving 10 respondents consisting of teachers and school staff to assess system usability and performance. The testing results indicate that the system is able to activate the school bell automatically according to the predefined schedule with a 100% success rate across all test scenarios. In addition, the system is equipped with a web-based interface that facilitates the management of bell schedules and active school days. The implementation of this system has proven to improve time accuracy and operational efficiency in academic activity management, thereby supporting the practical application of the Smart School concept.